2019
DOI: 10.1016/j.jval.2019.09.2255
|View full text |Cite
|
Sign up to set email alerts
|

Pns355 How Involved Should Payers Be in the Developments of Target Product Profile (Tpp), Product Development Plan (Pdp) and Design of Clinical Trials (Doct)

Abstract: 85% of respondents stated that greater PMA input into clinical development would improve future launches. Conclusions: PMA teams face fewer internal launch challenges, but difficulties remain during payer negotiations due to insufficient clinical data. There is a need to better integrate PMA input early in the clinical development process to make the necessary evidence available at launch, and effectively manage senior leadership expectations around price potential and the associated evidence requirements, par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Potential interactions between regulatory and HTA agencies have been suggested to converge clinical requirements, align national review and reimbursement process, and increase transparency and trust between stakeholders ( Centre for Innovation in Regulatory Science, 2021 ). A previous study also suggested that payers should be involved in TPP development, which can facilitate evidence generation and understanding of payer related issues and unmet medical needs ( Fatoye et al, 2019 ). Nevertheless, the advice provided by HTA agencies is non-binding and the treatment and reimbursement landscape may change by the time the product reaches market access; therefore, internal activities are also critical to enable good competitor intelligence and scenario planning.…”
Section: Discussionmentioning
confidence: 99%
“…Potential interactions between regulatory and HTA agencies have been suggested to converge clinical requirements, align national review and reimbursement process, and increase transparency and trust between stakeholders ( Centre for Innovation in Regulatory Science, 2021 ). A previous study also suggested that payers should be involved in TPP development, which can facilitate evidence generation and understanding of payer related issues and unmet medical needs ( Fatoye et al, 2019 ). Nevertheless, the advice provided by HTA agencies is non-binding and the treatment and reimbursement landscape may change by the time the product reaches market access; therefore, internal activities are also critical to enable good competitor intelligence and scenario planning.…”
Section: Discussionmentioning
confidence: 99%